An Analysis of the Effectiveness of Allocation of Village Fund Policy Implementation and Its Determining Factors in Gorontalo Regency - Ismet Sulila (Jurnal Ilmiah Ilmu Administrasi Publik, 2019)
Therefore, this study aims at examining the realization of the allocation of village fund, income per capita, and what factors determine the effectiveness of the implementation of village fund allocation policies in Gorontalo District. The complexity of implementing village fund policies requires caution in empirical studies in the field. Therefore the research approach uses qualitative methods. The data source in this study was primary data, which was conducted using a matrix of problem-based interview guidelines. Further, the data analysis techniques used consisted of data collection, data display, data condensation and verifying drawing conclusions. Data obtained in the field show that the allocation of village fund continues to increase. The impact of an increase in the allocation of village fund to the level of development in the village can be seen through per capita income in the last five years that has increased. Furthermore, the results of empirical studies in the field show that there are five important factors that determine the effectiveness of the implementation of village fund policies in Gorontalo District, namely 1) Participation, 2) communication, 3) resources, 4) attitude of implementers 5) organizational structure of implementers, 6) environment.